Los Factores Determinantes de las Condiciones de Pobreza en Ecuador: Análisis Empírico en Base a la Pobreza por Consumo - Castillo, José Gabriel (2007)
We analyze households” poverty conditions in Ecuador, not just from traditional approaches that quantify poverty levels, but from a detailed microeconomic perspective to identify more accurate the main determinants of poverty. We first, applied semilogarithmic estimation models to analyzed the factors that affects household?s consume levels. Then, using qualitative responsive models (probit) we look at the main poverty determinant's poverty conditions at the household level in Ecuador. This methodology is useful to identify policy recommendations that may guide institutional efforts, whether public or private, aim to fight poverty in the country.